STUDENT'S ABILITY TO USE RELATIVE CLAUSES IN WRITING COMPLEX SENTENCE AT MTs N 1 GUNUNG TULEH PASAMAN BARAT - zainuddin saragih (JURNAL LINER (Language Intelligence and Educational Research), 2022)
Abstract: This research aims to know the students' ability to use relative clauses in writing complex sentences, to understand students' difficulties in using relative clauses in writing complex sentences, and to know English teachers' efforts to overcome students' difficulties in writing complex sentences. The research happened in MTs N 1 Gunung Tuleh Pasaman Barat. The second-year students and English teachers were sources of data. Qualitative research with the descriptive method was a kind of research. The observation, interview, and test were the instruments of data collection. Then, the researcher knew that the student's ability to use the relative clause in writing a complex sentence at MTs N 1 Gunung Tuleh Pasaman Barat was in enough category, mean score of 44.4%. The student's difficulties in using the relative clause in writing complex sentences were poor vocabulary, a lack of master grammar, and a lack of knowledge of using relative clauses in writing a complex sentence. The efforts made by an English teacher to overcome the students' difficulties were repeating a lesson, giving an explanation, exercising, and being motivated. Keywords: relative clauses, complex sentences, writing